Foucauldian transgression as a mode of resistance in selected novels by Martin Amis - Mohammed, Marwan Kadhim (2017)
Transgression is a complex construction which varies in definitions, meanings and techniques. It is a social and cultural expression, usually related to violation and deviation, presented nearly in all genres of ancient and present literature. Although the study of transgression is now vast and emerging, literature of transgression remains a blind spot and only a little concern is given to its dimensions of identity formation and resistance. Moreover, Martin Amis, as a postmodern English writer, is widely recognized as transgressive in his writings. His works are widely labeled with ‘sexuality’ and ‘pornography’ in the past researches. Thus, the present study examines the social transgression in Martin Amis' selected novels in terms of Michel Foucault's theory of Transgression. Accordingly, the first objective is to examine the aspects of transgression in Amis’ selected novels by explaining the acts of crossing and going beyond Limits in order to liberate his discourse from labels of ‘sexuality’ and ‘pornography’. The second objective is to explore the role of transgression in the creation of counter-discourses via examining the characters’ Problematization of the common discourses that helps the characters to seek new definitions. The third objective is to explore the function of transgression as a mode of resistance in light of Discontinuity in the selected novels. The study is significant in the sense that it introduces a new perspective of reading social transgression in Amis' selected novels in an attempt to extend the definition and function of transgression in these novels. The contribution of the study lies in examining the non-traditional aspects of transgression which are essential in resisting common discourses and reconstituting subjectivity. Moreover, the study provides a valuable insight into how transgressive characters of the selected novels constitute themselves as resistant subjects out of the deeply- established norms of the society. Such trial may bridge the gap of the resistant dimension of transgression to provide a new perspective to transgressive literature in general and the selected novels in particular. The study conducted a detailed textual analysis of Amis' novels; Money (1984), London Fields (1989), Time's Arrow (1991), and The Pregnant Widow (2010). It concludes that social transgression in Amis' novels is not a simple violation of rules but rather an intended strategy of resisting the common discourses for the sake of circulating new ones of identity reconstitution. It liberates Amis' characters from restraining definitions of the self and transforms them from 'alienated', 'lost-identity', subjugated' and 'silenced' into 'empowered', 'self-defined', 'liberated' and 'voiced' subjects. Finally, the study contributes to the understanding of Amis' transgressive style via clearing up the labels of 'sexuality' and 'pornography' from his creative writings. It also contributes to the understanding of the role of transgression as a mode of resistance to common discourses of the society.